The impact of menstruation on participation in adventurous activities - Prince, Heather E.; Annison, Erin (Sport, education and society, 2023)
Menstruation is a 'taboo' subject in many cultures and its effect on women's participation in sport and physical culture in western societies is under-researched. This study examines the effect of menstruation and premenstrual syndrome (PMS) on habitual participants in adventurous activities through the voices of women. It transcends the social/biological divide using a theoretical framework to ascertain the personal, socio-cultural and practical constraints and enablers to participation. In a survey to explore women's lived experiences (n = 100), 89% of respondents noted that their participation is affected by menstruation/PMS. The dominant constraints to participation in adventurous activities were related to practical challenges of hygiene and waste disposal for managing menstruation. Rich qualitative data provide evidence for the negative and emotional responses of women to 'missing out' on adventurous activities with the majority of concerns about their performance in socio-cultural contexts related to personal anxieties. Some women commented on their belief in being a role model in professional work encouraging open discussion around menstruation and enabling more women and girls to take part in adventurous activities. Key practical recommendations for practice are suggested in respect of provision of toilet facilities where possible and biodegradable sanitary products. Raised awareness amongst leaders and educators, particularly men is important so that they might identify strategies to manage the constraints facing women and girls and enable more inclusivity and greater participation in adventurous activities.